Friendly Alien: Object and Interface - Lev Manovich (Artifact, 2007)
Abstract Since 1996, artist Miltos Manetas has done paintings that systematically portray the new essential objects of contemporary life: joysticks, computers, computer game consoles, and computer cables (lots of them). Manetas also paints people who are usually intensely engaged in the activities made possible by consumer electronics devices, such as playing a computer game. But he never shows what games they are playing or what images they are looking at. Instead, he focuses on the humancomputer interface: hands clutching a joystick, a body stretched across the floor in the intense concentration or, alternatively, relaxing besides a laptop, a computer console, or a TV.